Influence of geometrical parameters on the dynamic characteristics of thin vertical clamped free cylindrical shell - Lejano, Bernardo A. (Philippine Engineering Journal)
Recently the demand to build bigger and taller cylindrical shell structures has increased. This is accompanied with susceptibility to earthquake and wind vibrations. Hence, the design of such structures must ensure safety against these dynamic loads. Dynamic performance of structures is reflected in the dynamic characteristics. A finite element program suitable for the evaluation of the dynamic characteristics of cylindrical shell was developed for a 640K personal computer. The influence of geometrical parameters on the dynamic characteristics of the cylindrical shell was investigated using the said computer program.